First Report of the Stapled Mesh Stoma Reinforcement Technique in a Urologic Context - Dwayne Tun Soong Chang; Isaac Andrew Thyer; John Oliver Larkin; Marina Helen Wallace; Dickon Hayne (Case Reports in Urology)
Parastomal hernia is a common complication of ileal conduit formation. Mesh repair of parastomal hernia has lower rate of recurrence than nonmesh techniques but can be time-consuming to perform. The stapled mesh stoma reinforcement technique (SMART) is a novel method of rapidly constructing a reinforced stapled stoma. We report the first case utilising this technique in a urologic context. The procedure was performed on a middle-aged female with recurrent parastomal hernia of her ileal conduit. There were no perioperative complications. The resited stoma remained healthy and functioned normally. Longer term data is clearly desirable though this technique deserves consideration in the treatment of urologic parastomal hernias. This case demonstrates that SMART is an easy and convenient procedure for parastomal hernia repair.